2010
DOI: 10.1007/s11842-010-9110-6
|View full text |Cite
|
Sign up to set email alerts
|

Why Certify? Motivations, Outcomes and the Importance of Facilitating Organizations in Certification of Community-Based Forestry Initiatives

Abstract: Despite documented challenges, many community-based forestry (CBF) initiatives pursue forest certification. This study asked community-based forestry practitioners in Vermont what influenced their decisions to seek or not seek certification and what outcomes were realized from certification. Relationships, public image, value alignment and feedback on management practices were most commonly cited as both motivations for and results of certification. Expectations for economic benefits were low and price premium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…Studies on the drivers and motivations of forest companies to pursue for certification have been conducted in many regions (e.g., Argentina, Bolivia, Brazil, Canada, China, Mexico, Rusia and USA) for different types of forestry firms including community forests (Crow and Danks 2010, Humphries & Kainer 2006, Humphries 2010, Ward 2013) and industrial companies (Araujo et al 2009, Auld et al 2003, Chen et al 2011, Espinoza and Dockry 2014, Owari et al 2006, Trishkin et al 2014. Most of these studies reported that the perception of non-economic benefits represented the dominant motivations for the pursuit of certification, but were influenced heavily by local contexts (e.g., local timber market, government regulation and forest company structure, natural disasters).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the drivers and motivations of forest companies to pursue for certification have been conducted in many regions (e.g., Argentina, Bolivia, Brazil, Canada, China, Mexico, Rusia and USA) for different types of forestry firms including community forests (Crow and Danks 2010, Humphries & Kainer 2006, Humphries 2010, Ward 2013) and industrial companies (Araujo et al 2009, Auld et al 2003, Chen et al 2011, Espinoza and Dockry 2014, Owari et al 2006, Trishkin et al 2014. Most of these studies reported that the perception of non-economic benefits represented the dominant motivations for the pursuit of certification, but were influenced heavily by local contexts (e.g., local timber market, government regulation and forest company structure, natural disasters).…”
Section: Discussionmentioning
confidence: 99%
“…It was surprising that audit costs were not considered as major by the majority of stakeholders. In many other studies, particularly in community forests, audits represent a big share of the total cost (e.g., Alemagi et al 2011, Crow and Danks 2010, Hartsfield and Ostermeier 2003, Humphries and Kainer 2006. This difference is probably due to the fact that in Indonesia this cost is covered by external funding and because it is small relative to the operational costs of a large industrial FMU (see Ruslandi et al 2014).…”
Section: Expected Benefits and Major Costs Of Certificationmentioning
confidence: 99%
See 1 more Smart Citation
“…La position d'une UFA sur le continuum de certification (Figure 4) (Nebel et al 2005 ;Kollert et Lagan 2007 ;Crow et Danks 2010 ;Chen et al 2011b). La compréhension approfondie de ces phénomènes permettra de découvrir les impacts véritables de la certification de la gestion forestière.…”
Section: Connaissances De La Dynamique Temporelle De La Certificationunclassified
“…Market dynamics (e.g., consumer preferences and acquisition power) change and, in turn, influence suppliers' decisions vis à vis certification. Shifting legal frameworks and their enforcement, technical capacities, technological innovations, global/regional/national economic conditions and cost-benefit ratios are among the factors that can affect FMU decisions 4 Knowledge needs for the design of an evaluation of the impacts of forest management certification about remaining certified or not (Nebel et al 2005;Kollert and Lagan 2007;Crow and Danks 2010;Chen et al 2011b). Substantial understanding of these dynamics will reveal the true impacts of forest management certification.…”
Section: Knowledge About the Temporal Dynamics Of Certificationmentioning
confidence: 99%